Multicentre evaluation of renal impairment in thoracic surgery (MERITS): a retrospective cohort study. Issue 9 (27th September 2022) - Naruka, Vinci; McKie, Mikel Alexander; Ahmadi, Navid; Pama, E A Claudia; Coonar, Aman S; Collaborators, MERITS
Abstract : Objectives: To measure the unit-level variation in Acute Kidney Injury (AKI) incidence post-thoracic surgery over a contemporary 1-year period. Secondary aims include examining the associations with sex, age group, operation type, length of stay and mortality. Design: A multicentre, observational, retrospective study in thoracic surgery. Setting: 17 of 35 Society for Cardiothoracic Surgery of Great Britain and Ireland (SCTS) units participated. The student wing, known as SCTS STUDENTS, supported data collection. Participants: Overall, 15 229 patients were collected of which 15 154 were included for analysis after exclusions. All patients (age≥18 years) undergoing any thoracic surgery from 1 April 2016 to 31 March 2017 were included. For analysis, we excluded patients with preoperative end-stage renal failure and those with incomplete data. Main outcome measures: The primary outcome is the incidence of AKI within 7 days of the procedure or discharge date if earlier. Secondary outcomes include assessing associations with patient demographics (age, sex), type of procedure (open and minimally invasive), length of stay and mortality. Results: Out of 15 154 patients AKI was diagnosed in 1090 patients (7.2%) within 7 days of surgery with AKI stage 1 (4.8%), stage 2 (1.7%) and stage 3 (0.7%). There was a statistically significant variation in AKI incidence between units from 3.1 to 16.1% (p<0.05). Significant differences between AKI and non-AKI were found in post-operative length of stay (7 vs 3 days, p<0.001), 30-day mortality (9 vs 1.6%, p<0.001), 90-day mortality (14.7 vs 4.4%, p<0.001) and 1-year mortality (23.1 vs 12.2 %, p<0.001). Conclusions: Following thoracic surgery, AKI incidence ranged from 3.1% to 16.1% between units (p<0.05) with associations between AKI and both length of stay and mortality. We propose AKI as a suitable comparative and absolute quality measure in thoracic surgery. Reducing rates of AKI may improve patient outcomes, length of stay and reduce costs.